Duopoly price competition with limited capacity - A. Bërdëllima (Economic Theory Bulletin, 2021)
We study a variation of the duopoly model by Kreps and Scheinkman (1983). Firms limited by their capacity of production engage in a two stage game. In the first stage they commit to levels of production not exceeding their capacities which are then made common knowledge. In the second stage after production has taken place firms simultaneously compete in prices. Solution of this sequential game shows that the unique Cournot equilibrium outcome as in Kreps and Scheinkman is not always guaranteed. However the Cournot outcome is still robust in the sense that given sufficiently large capacities this equilibrium holds. If capacities are sufficiently small, firms decide to produce at their full capacity and set a price which clears the market at the given level of output.
Keywords: D40; D43; L10; L11; L13; L20; 330; Capacity; Cournot; Duopoly competition; Nash equilibrium; Sequential game